PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN (Studi Kasus Pada Perusahaan Manufaktur Sektor Otomotif dan Komponen Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2013) - Astuti, Wati Aris; Nurpadilah, Itsna (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2015)
This study aims to determine how much influence the profitability of thedividend policy on the automotive sector and manufacturing companies of componentslisted in the Indonesia Stock Exchange.The method used in this research is descriptive analysis and verification.Statistical tests used in the multiple regression analysis through the testing phaseclassical assumption test, regression analysis, partial correlation analysis, coefficient ofdetermination and hypothesis testing using SPSS V.21 .1 for windows.Results of testing the hypothesis in this study show that changes in theprofitability of significant and positive impact on dividend policy on the automotivesector and manufacturing companies of components listed in the Indonesia StockExchange.